Evaluation on the performances of a micro gas turbine, gas engine-cogeneration system in sewage treatment plant - Mohamad Arif, Roslan (2013)
This paper provides an overview on the characterization of the efficiency and emissions from small-scale cogeneration systems, with specific reference to the prime movers technologies nowadays most available in the market, namely, micro gas turbine and gas engines. The corresponding environmental impacts are evaluated by using the emission balance approach. A numerical case study with two representative machines highlights their different emission characteristics, also considering the partial -load emission performance. Power produced from micro gas turbine and gas engine will supply to power demand while heat from both of cogeneration as stated above will undergo heat exchanger to produce heat exhaust heat recovery, Qehr. Emission and efficiency data are obtained from the journal. It calculated by using formula to calculate efficiency of the systems. In order to get the best configuration of cogeneration in sewage treatment plants in term of efficiency and emission there is one system. By using the micro gas turbine as a base that run on full load while gas engine run on partial load, two emission reduced to 20% from its original volume of 1st month, they are nitrogen oxide and carbon monoxide. Nitrogen oxide emission from 48x10kgreduced to 38x103kg and Carbon monoxide from 1.5x107kg to 11964340 kg. Forefficiency it increases by 2.33% from previous efficiency.